The Linkage between Breast Cancer, Hypoxia, and Adipose Tissue - Rausch, Linda K.; Netzer, Nikolaus C.; Hoegel, Josef; Pramsohler, Stephan (Frontiers in Oncology, 2017)
The development of breast cancer cells is linked to hypoxia. The hypoxia-induced-factor HIF-1α influences metastasis through neovascularization. Hypoxia seems to decrease the responsiveness to hormonal treatment due to loss of estrogen receptors. Obesity is discussed to increase hypoxia in adipocytes, which promotes a favorable environment for tumor cells in mammary fat tissue, whereas, tumor cells profit from good oxygen supply and are influenced by its deprivation as target regions within tumors show. This review gives an overview of the current state on research of hypoxia and breast cancer in human adipose tissue. Methods: A systematic literature search was conducted on PubMed (2000 – 2016) by applying hypoxia and/or adipocytes and breast cancer as keywords. Review articles were excluded as well as languages other than English or German. There was no restriction regarding the study design or type of breast cancer. A total of 35 papers were found. 8 studies were excluded due to missing at least 2 of the 3 keywords. 1 paper was removed due to Russian language, and one was dismissed due to lack of adherence. 7 papers were identified as reviews. After applying exclusion criteria, 18 articles were eligible for inclusion. Results: 2 articles describe the impairment of mammary epithelial cell polarization through hypoxic preconditioning. A high amount of adipocytes enhances cancer progression due to the increased expression of HIF-1α which causes the loss of estrogen receptor α protein as stated in 4 articles. Four articles analyzed that increased activation of HIF’s induces a series of transcriptions resulting in tumor angiogenesis. HIF inhibition, especially when combined with cytotoxic chemotherapy, holds strong potential for tumor suppression as stated in further 4 articles. In 2 articles there is evidence of a strong connection between hypoxia, oxidative stress and a poor prognosis for breast cancer via HIF regulated pathways. Acute hypoxia seems to normalize the microenvironment in breast cancer tissue and has proven to affect tumor growth positively as covered in 2 articles. Conclusion: This review indicates that the development of breast cancer is influenced by hypoxia. A high amount of adipocytes enhances cancer progression due to the increased expression